Performance Evaluation of Commercial Lost Circulation Materials - Idress, M. (Elsevier Ltd, 2019)
Lost circulation can be considered as one of the crucial drilling problems during drilling a hydrocarbon well and can cause a lot of negative consequences including formation damage, loss of well and requires a lot of money to solve this problem. There are many ways to mitigate this issue and one of them is to use lost circulation materials and mix together with the drilling fluids. However, there are many types of lost circulation materials and their performance varies depending on the condition. Some of the most common commercial lost circulation materials are nut plug and corn cob. In this paper, the evaluation of these two materials were studied and laboratory investigation was done to evaluate the performance in terms of rheology and filtration properties. The samples were prepared and mixed in the water-based drilling fluid with different sizes (fine, medium and coarse) and another drilling fluid were also prepared with combination of fine and medium sizes of the samples. The density, rheology and filtration properties of the mud were tested by using pressurized mud balance, viscometer and filtration tester respectively. The results show that there is no exact difference in terms of plastic viscosity, yield point and gel strength between nut plug and corn cob. However, nut plug shows a slightly higher result compared to corn cob in those three parameters. In terms of filtration properties, nut plug shows less filtrates produced while compared to corn cob but mud cake produced by corn cob is slightly thinner than nut plug. In terms of sizes, fine sizes of nut plug and corn cob yield better filtration properties compared to other sizes. However, the filtration results are better when fine and medium sizes of the nut plug and corn cob samples were combined together. In conclusion, the correct sizes of the lost circulation materials should be determined and chosen properly in order to get good performance of the drilling fluids. Â© 2019 Elsevier Ltd.